Early hyperreactive malarial splenomegaly and risk factors for evolution into the full-blown syndrome: a single-centre, retrospective, longitudinal study. (December 2015) - Bisoffi, Zeno; Leoni, Stefania; Buonfrate, Dora; Lodesani, Claudia; Eseme, Franklin; Monteiro, Geraldo; Marocco, Stefania; Guerriero, Massimo
Abstract Background The hyperreactive malarial splenomegaly (HMS) represents a chronic, potentially fatal complication of malaria. Case definition includes: gross splenomegaly, high level of anti-malarial antibody and IgM, response to long-term anti-malarial prophylaxis. In this study, a large series of patients not fully meeting the case definition was tentatively classified as early hyperreactive malarial splenomegaly (e-HMS). The main research questions was: does "e-HMS" tend to evolve to the full-blown syndrome? And if so, what are the main factors influencing this evolution? Methods Retrospective, longitudinal study. The patient database was searched to retrieve all potentially eligible patients. e-HMS was defined by splenomegaly of any size (with or without raised IgM), high anti-malarial antibody titre and exclusion of other causes of splenomegaly. The clinical outcome at following visits was analysed in relation to re-exposure to malaria, and to treatment (only part of the patients with e-HMS were treated with a single anti-malarial treatment and advised to follow an effective anti-malarial prophylaxis, if re-exposed). The association of the outcome with the main independent variables was first assessed with univariate analysis. A stepwise logistic regression model was then performed to study the association of the outcome with the main independent variables. Results One hundred and twenty-six subjects with e-HMS were retrieved. Eighty-one had at least one follow-up visit. Of 46 re-exposed to malaria for a variable period, 21 (46 %) had progressed, including 10/46 (22 %) evolving to full-blown HMS, while of 29 patients not re-exposed, 24 (93 %) had improved or cured and five (7 %) progressed (p < 0.001). At logistic regression re-exposure was confirmed as a major risk factor of progression (OR 9.458, CI 1.767–50.616) while treatment at initial visit was protective (OR 0.187, CI 0.054–0.650). Conclusion e-HMS should be regarded as a clinical condition predisposing to HMS. Although the case definition may include false positives, e-HMS should be treated just as the full-blown syndrome. A single anti-malarial treatment is probably adequate, followed by effective prophylaxis for patients exposed again to malaria transmission.